Social Media Impact: Utility of Reflective Approach in the Practice of Surgery - Mohiuddin, Zia (Indian J Surg, 2014)
Social media is rapidly being incorporated into medical education. We created a small group, reflective practice sessions by integrating specific medical cases to improve awareness about professionalism on social media. Medical scenarios were generated for reflective practice sessions on social media professionalism. Anonymous pre/post-session surveys evaluated residents' use of social media and gathered their opinions on the session. Thirty-eight of 48 (79 %) residents replied to the presession survey with 50 % (19/38) reporting daily digital media use, 76 % (29/38) witnessed unprofessional postings on social media, and 21 % (8/38) posted unprofessional content themselves. Of the 79 % (30/38) residents who attended the session, 74 % (28/38) completed the post-session survey. Residents reported the session added to the longevity of their professional career 4.11, 95 % CI (3.89–4.36). As a result of the session, they were more conscious of using the social media more professionally 3.47, 95 % CI (2.88–3.96) and would be proactive in protecting patient privacy and confidentiality on social media sites 3.96, 95 % CI (3.50–4.37). In summary, reflective practice-based sessions regarding the impact of social media on professionalism in surgery was well favored by the residents. The majority agreed that it had important implications for the longevity of their professional career. Participants reported having an increased awareness to protect patient privacy and utilize social media more professionally.